2018
DOI: 10.1088/1361-6463/aae807
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and antibacterial effects of plasma activated water: correlation with gaseous and aqueous reactive oxygen and nitrogen species, plasma sources and air flow conditions

Abstract: When cold atmospheric plasma comes into contact with water and biological media, antimicrobial or antitumor effects are induced, representing great potential for applications in biomedicine and agriculture. The need to control and tune the chemical composition and biomedical effects of plasma activated water/media (PAW/PAM) is emerging. By comparing two nonthermal air plasma sources, streamer corona and transient spark, interacting with water in open and closed reactors, and by enhancing the plasma-liquid inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
204
1
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(245 citation statements)
references
References 68 publications
7
204
1
7
Order By: Relevance
“…It was found that the number of surviving E. coli was about 2 × 10 3 mL −1 after direct plasma treatment for 10 s and decreased to the colony counting method detection limit of 10 mL 1 after 30 s, showing a 6-log reduction in the concentration of bacteria. As shown in Figure 8, the bactericidal effect of treatment with AALCA was significantly higher than the bactericidal effect of treatment with NEAPRS and APPJ, corona, or DBD discharges reported elsewhere [9,43,[49][50][51][52][53][54][55][56]. It was confirmed by thermographic observation that the suspension was heated by irradiation to temperatures up to 38 • C, which is below the temperature harmful for E. coli reported elsewhere, suggesting that heating of the sample was not involved in the sterilization process [57].…”
Section: Inactivation Of E Colimentioning
confidence: 58%
“…It was found that the number of surviving E. coli was about 2 × 10 3 mL −1 after direct plasma treatment for 10 s and decreased to the colony counting method detection limit of 10 mL 1 after 30 s, showing a 6-log reduction in the concentration of bacteria. As shown in Figure 8, the bactericidal effect of treatment with AALCA was significantly higher than the bactericidal effect of treatment with NEAPRS and APPJ, corona, or DBD discharges reported elsewhere [9,43,[49][50][51][52][53][54][55][56]. It was confirmed by thermographic observation that the suspension was heated by irradiation to temperatures up to 38 • C, which is below the temperature harmful for E. coli reported elsewhere, suggesting that heating of the sample was not involved in the sterilization process [57].…”
Section: Inactivation Of E Colimentioning
confidence: 58%
“…In the nitrogen discharge, the electron‐impact dissociation of N 2 will produce ground state N ( 2 D), N ( 2 P), and N ( 4 S), and then produce the excited state N (3 p ) via the electron‐impact excitation processes . The related reactions are shown as R1–R3 in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The related reactions are shown as R1–R3 in Table . Ground state H atoms are generated through the electron dissociation of H 2 O, and excited to H ( n = 3) by electron excitation processes (see R4 and R5) . The quenching processes of metastable N 2 (A) or N atoms by H 2 O are other pathways to generate H atom (see R6 and R7) .…”
Section: Resultsmentioning
confidence: 99%
“…The emission spectra, showing atomic oxygen, atomic hydrogen and excited nitrogen molecules/ions in the discharge, clearly indicate that water vapour molecules were dissociated to OH radicals. The presence of excited nitrogen molecules and atomic oxygen also suggests the presence of nitrogen oxide species [23], commonly observed in discharge spectra of discharges used to produce RONS in water [24,25]. While other spectroscopic methods (e.g., Fourier transform infrared absorption, laser absorption, electron paramagnetic resonance), along with fluorescence/colorimetric measurements [22,26,27], may be better placed to confirm and quantify RONS, our own spectroscopic evaluation clearly showed production of RONS by HC + plasma.…”
Section: Microcystis Growth Inhibition Under Optimal Conditions With mentioning
confidence: 99%